PENANAMAN NILAI PENDIDIKAN KARAKTER MELALUI KEGIATAN MEMBACA DONGENG SISWA KELAS III MI NU ISLAMIYAH ASEMBAGUS - Nani Farah Fasica (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2018)
This study aims to determine values of character education attached in the tales of Si Kancil and Si Rusa, in addition this research to discuss students ability in understanding the characters by reading activities for students of third grade MINU Islamiyah Asembagus. During learning process of reading, reseacher engaged descriptive qualitative method. Data was collected based on classroom observation and interview. Research results indicate that values upon the takes of Si Kancil and SI Rusa are genuine, humble, and mutual help. While the message of Si Kancil and Si Rusa is do not lie to the others, since it harm, which the message of Si Rusa and Kulomang is good cooperation will work in overcoming many obstacles. Character values of both tales frequently appear are being honest, humble, and giving each other support. Therefore, those characters are much suitable to be educated since early age. By reading activities performed in third grade students MINU Islamiya Asemabagus obtained a conclusion that during tale reading activities, teacher plays role as facilitator to assist students in grasping character values which can be implemented in daily life